A novel measure of matching categories for early development: Item creation and pilot feasibility study. (August 2021) - Condy, Emma; Kaat, Aaron J.; Becker, Lindsey; Sullivan, Nancy; Soorya, Latha; Berger, Natalie; Berry-Kravis, Elizabeth; Michalak, Claire; Thurm, Audrey
Highlights: Concept formation is a cognitive domain and a prerequisite to more advanced skills. We summarize the development of a tablet-based concept formation test. The test described will use a computer adaptive testing format to test children. Feasibility of this novel measure is reported for children with developmental delays. Abstract: Background: Many cognitive tests assess a limited developmental span, making longitudinal measurement for trials aimed at improving cognition challenging. Tests targeting transitional skills, which integrate foundational abilities into complex schemas, may be amenable to assessment across a wide developmental span. Furthermore, tablet-based tests permit computer adaptive testing (CAT), which is psychometrically more efficient and could increase testing motivation, especially for children with developmental delays. Such measures may be useful for research and clinical practice. Aims: Outline the creation of a novel, tablet-based concept formation test, and evaluate its feasibility in individuals with mental ages less than 24-months. Methods and procedures: Item generation, user interface construction, and pre-piloting were conducted in consultation with subject matter experts. Item content and interface parameters underwent iterative revisions, resulting in the pilot test. Outcomes and results: We created and piloted a tablet-based test of concept formation suitable for CAT-based administration with items of increasing difficulty based on target salience. We show feasibility in individuals with mental ages less than 24-months-old. Conclusions and implications: Tablet-based assessment of concept formation may be a useful outcome measure of an aspect of cognitive ability in young children. Future work will address optimizing the user interface and developing CAT administration.